The relationship between the relative GDP share of agriculture and the unemployment rate in selected Central and Eastern European countries - Bein, Murad A.; Ciftcioglu, Serhan (Czech Academy Agricultural Sciences, 2017)
The study empirically investigates the relationship between the relative GDP share of agriculture and the unemployment rate in a sample of ten Central and Eastern European countries. Utilising the annual data for the sample period 1996-2013, the empirical analysis is carried out using the dynamic panel regression analysis and the Granger causality tests. The estimation results based on the alternative specification of regression equations for the unemployment rate suggest that the unemployment rate is negatively related to the relative GDP share of agriculture. In addition, a similar effect has been obtained for some other explanatory variables we have included in the unemployment equation as controlling variables: higher investment rate and trade openness are likely to lower the rate of unemployment. The financial development has also been found to be negatively related to the unemployment rate, although the statistical significance of its effect depends on the estimation technique used. On the other hand, the GDP growth and the government consumption have been found to be insignificantly related to the unemployment rate. While the Granger causality tests performed for each country produced evidence of a causal effect of the relative GDP share of agriculture in some countries, in some other countries the direction of causality has been found to be from the unemployment rate to the relative GDP share of agriculture. Our findings suggest that agriculture may play a potential role in lowering the prevailing rates of high unemployment; but this potential is likely to vary between countries.
Keywords: dynamic panel regression; Granger causality; investment; trade openness